Porcine model of neurocysticercosis by intracarotid injection of Taenia solium oncospheres: Dose assessment, infection outcomes and serological responses - Gianfranco Arroyo; Luz Toribio; Ana Vargas-Calla; Juan F. Calcina; Edson Bernal; Nancy Chile; Miguel Zambrano; Luis A. Gomez-Puerta; Juan Chacaltana; Miguel Marzal; Javier A. Bustos; Manuela R. Verastegui; et al. (Public Library of Science (PLoS), 2022)
Background Neurocysticercosis (NCC) is the infection of the human central nervous system (CNS) by Taenia solium larvae that cause significant neurological morbidity. Studies on NCC pathophysiology, host-parasite interactions or therapeutic agents are limited by the lack of suitable animal models. We have previously reported that carotid injection of activated T. solium oncospheres directs parasites into the CNS and consistently reproduces NCC. This study assessed the minimal dose required to consistently obtain NCC by intracarotid oncosphere injection and compared antigen and antibody response profiles by dose-group. Methods/Principal findings Three groups of pigs were infected with either 2500 (n = 10), 5000 (n = 11), or 10000 (n = 10) oncospheres. Two pigs died during the study. Necropsy exam at day 150 post-infection (PI) demonstrated viable NCC in 21/29 pigs (72.4%), with higher NCC rates with increasing oncosphere doses (4/9 [44.4%], 9/11 [81.8%] and 8/9 [88.9%] for 2500, 5000, and 10000 oncospheres respectively, P for trend = 0.035). CNS cyst burden was also higher in pigs with increasing doses (P for trend = 0.008). Viable and degenerated muscle cysticerci were also found in all pigs, with degenerated cysticerci more frequent in the 2500 oncosphere dose-group. All pigs were positive for circulating parasite antigens on ELISA (Ag-ELISA) from day 14 PI; circulating antigens markedly increased at day 30 PI and remained high with plateau levels in pigs infected with either 5000 or 10000 oncospheres, but not in pigs infected with 2500 oncospheres. Specific antibodies appeared at day 30 PI and were not different between dose-groups. Conclusion/Significance Intracarotid injection of 5000 or more oncospheres produces high NCC rates in pigs with CNS cyst burdens like those usually found in human NCC, making this model appropriate for studies on the pathogenesis of NCC and the effects of antiparasitic treatment. Author summary Neurocysticercosis (NCC) is the infection of the central nervous system (CNS) with Taenia solium larvae and is considered a neglected disease that causes significant neurological morbidity in humans. Animal models are essential to better understand the pathophysiological processes that occur during NCC infection, disease progression and to evaluate the effects of antiparasitic treatment. Here, we demonstrated that by injecting 5000 or more activated T. solium oncospheres into the carotid artery of pigs we consistently reproduced NCC in a number that closely resemble human infection. All cysticerci found in the CNS were apparently viable, whereas in the musculature viable and degenerated cysticerci were found. Serum antigens in experimentally infected pigs were detected as early as 14 days post-infection and remained high in NCC pigs until necropsy. Histological analysis of brain cysticerci showed different degrees of inflammatory cell infiltration adjacent to the cyst wall, mostly composed of eosinophils, lymphocytes, and macrophages, whereas most of the cysticerci were apparently intact with cyst wall and neck without damage. Our findings demonstrated that the intracarotid pig model is suitable for studies on the pathogenesis and antiparasitic treatment in NCC.